A real-time virtual liver simulator using position based dynamics with compliant constraints for medical applications - Yufan Guo; Dongliang Kou; Xukun Zhang; Lihua Zhang; Kai Cao (Scientific Reports)
Abstract Liver simulation serves as a crucial foundation for precise preoperative planning and intraoperative navigation, with its accuracy and real-time performance directly impacting the safety and efficiency of surgical procedures. However, existing physical simulation techniques face a trade-off between high precision with slow computational speeds and rapid performance with diminished accuracy. This imbalance restricts their utility in dynamic surgical environments that demand both accuracy and real-time interaction. To overcome this limitation, we present a novel real-time liver simulation algorithm leveraging Extended Position-Based Dynamics (XPBD). Our approach integrates four well-formulated physical constraints–Distance, Volume, Shape Matching, and the Neo-Hookean model–within a proprietary, high-efficiency physics engine, achieving high-precision, real-time simulation of hepatic geometric deformations and mechanical properties. Experimental evaluations reveal that our method not only meets the stringent real-time requirements of surgical procedures but also significantly enhances the visual realism and stability of simulations. This advancement demonstrates substantial potential for extensive applications in preoperative planning, intraoperative navigation, and medical training.